THE DISSOLUTION OF APATITE IN THE PRESENCE OF AQUEOUS METAL CATIONS AT PH 2-7 - Valsami-Jones E.; Ragnarsdottir K.V.; Putnis A.; Bosbach D.; Kemp A.J.; Cressey G. (My University, 1998)
Apatite dissolution was studied at 25°C in a series of batch experiments carried out within the pH range of 2-7 with or without the presence of aqueous Pb2+ or Cd2+. The synthetic, microcrystalline hydroxylapatite used in the majority of the experiments was found to have a significantly higher solubility than natural fluorapatite, but a lower dissolution rate. The dissolution rates of both phases increased with decreasing pH. When Pb2+ was present in solution in contact with synthetic hydroxylapatite its concentration decreased over a time interval ranging from several days to several weeks, to a steady state minimum. The rate of Pb2+ loss from solution was sensitive to acidity, and progressed faster at lower pH, but maximum loss was independent of pH. Calcium release to solution matched aqueous lead loss on a mole for mole basis. By the end of each experiment mass calculations suggest that all apatite had been consumed regardless of reaction rate and pH. The solid residue was newly crystallised Pb-hydroxylapatite. This reaction was also observed in situ using Atomic Force Microscopy (AFM) and was found to take place epitaxially onto apatite surfaces. The concentration of aqueous Cd2+ in solution was also reduced in the presence of hydroxylapatite. Cadmium losses were, however, substantially lower. Unlike Pb2+, the maximum amount of Cd2+ lost from solution was a function of pH, and was higher as solution composition approached neutral pH. Cadmium was present in the solid residue at the end of these experiments, probably as a Ca-Cd phosphate solid solution. This work suggests that the interaction between apatite and metals in solution is controlled by apatite dissolution and results in the precipitation of new metal phosphates. The new phosphates nucleate heterogeneously onto the hydroxylapatite surfaces, which acts as a catalyst for the reaction.
Keywords: APATITE; DISSOLUTION; SOLUBILITY; PHOSPHATES; METALS; LEAD; CADMIUM